EFFECT OF GY LEAF SPOT ON OIL CONTENT OF RAPESEED AND MUSTARD: Short Communication (Biological Sciences - PJSIR, 2002)
Grey leaf spot (GLS) is an economically important fungaldisease of rapeseed and mustard in many parts of the world.Alternaria brassicae (Berk.) sacc. the causal agent of GLS isa necrotrophic pathogen and can produce conspicuousspotting of all aerial plant parts depending on the host reactionand environmental conditions (Kolte 1985 and Connet al 1990). There are conflicting reports on the effect ofA.brassicae on the oil content of Bras sica spp. seeds (Stovoldet al1987 and Seidle et aI1995). The present study was thereforeundertaken to examine this conflicting and unaddressedproblems of rapeseed and mustard in Pakistan due to severeedible oil crises in the country.